2018
DOI: 10.1111/ecc.12861
|View full text |Cite
|
Sign up to set email alerts
|

Changes in metabolic risk, insulin resistance, leptin and adiponectin following a lifestyle intervention in overweight and obese breast cancer survivors

Abstract: Adiposity and physical activity are modifiable factors that could be important determinants of breast cancer (BC) prognosis through their effects on endogenous reproductive hormones, chronic inflammation and metabolic changes. Therefore, it is necessary to evaluate whether offering lifestyle interventions to BC survivors could affect the levels of certain biomarkers involved in these mechanisms. We designed a pre-post intervention study offering diet and exercise sessions over 12 weeks to 42 overweight/obese B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 43 publications
(119 reference statements)
0
24
0
Order By: Relevance
“…It is difficult to distinguish the effects of ET from nutrition-related improvements, as trials thus far have not included separate ET and diet intervention groups. This is particularly relevant, as these trials reported CRF as relative peak VO 2 and also reported decreases in weight, in which dietary intervention may play a larger role [152][153][154].…”
Section: Future Directionsmentioning
confidence: 97%
See 1 more Smart Citation
“…It is difficult to distinguish the effects of ET from nutrition-related improvements, as trials thus far have not included separate ET and diet intervention groups. This is particularly relevant, as these trials reported CRF as relative peak VO 2 and also reported decreases in weight, in which dietary intervention may play a larger role [152][153][154].…”
Section: Future Directionsmentioning
confidence: 97%
“…), can lead to significantly reduced exercise tolerance [146]. Several recent trials in cancer survivors have found that lifestyle interventions combining dietary counseling and PA/ET have been able to improve relative peak VO 2 compared to usual care [152,153] and in comparison to subjects' baseline [154]. It is difficult to distinguish the effects of ET from nutrition-related improvements, as trials thus far have not included separate ET and diet intervention groups.…”
Section: Future Directionsmentioning
confidence: 99%
“…Although it remains unclear how healthy lifestyle behaviors contribute to the improvement in quality of life in cancer survivors, modifications in insulin-like growth factor (IGF) actions [40][41][42][43] and decreased insulin resistance [44,45] may be potential mechanisms. The potential link of lifestyle factors to breast cancer risk or prognosis through IGF-1 signaling and the insulin resistance pathway has been suggested in several studies [40][41][42][43][44][45]. A few intervention studies on breast cancer survivors showed that a healthy diet and exercise modified the levels of IGF-1 and insulin resistance-related markers [40,44].…”
Section: Discussionmentioning
confidence: 99%
“…The potential link of lifestyle factors to breast cancer risk or prognosis through IGF-1 signaling and the insulin resistance pathway has been suggested in several studies [40][41][42][43][44][45]. A few intervention studies on breast cancer survivors showed that a healthy diet and exercise modified the levels of IGF-1 and insulin resistance-related markers [40,44]. A randomized controlled trial of postmenopausal breast cancer survivors found that aerobic exercise decreased IGF-1 and insulin-like growth factor-binding protein-3 (IGFBP-3), a predominant binding protein for IGF-1 [40].…”
Section: Discussionmentioning
confidence: 99%
“…Travier et al. (), in their pre‐ and postintervention study, add further to the evidence that diet and exercise interventions can impact favourably on metabolic risk biomarkers in patients with cancer—in this case also improving indicators of insulin resistance.…”
mentioning
confidence: 95%